2008
DOI: 10.4049/jimmunol.180.10.6836
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Pathology and Prolonged Survival of Human DC-SIGN Transgenic Mice during Mycobacterial Infection

Abstract: Dendritic cell (DC)-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN: CD209) is a C-type lectin that binds ICAM-2,3 and various pathogens such as HIV, helicobacter, and mycobacteria. It has been suggested that Mycobacterium tuberculosis, the causative agent of pulmonary tuberculosis, interacts with DC-SIGN to evade the immune system. To directly analyze the role of human DC-SIGN during mycobacterial infection, we generated conventional transgenic (tg) mice (termed "hSIGN") using CD209 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 67 publications
(44 reference statements)
2
68
0
Order By: Relevance
“…Therefore, M-CSF might drive the expression of DC-SIGN in tissue-resident macrophages in noninflamed tissues (homeostasis). Along this line, the ability of fibroblasts to modulate DC-SIGN expression on monocytes in an M-CSF-dependent manner (this manuscript), and the increased tissue repair and homeostasis observed in transgenic DC-SIGN mice after eradication of infectious agents (48), further support such a hypothesis.…”
Section: Dc-sign Expression On Tam Might Contribute To Maintenance Ofsupporting
confidence: 53%
“…Therefore, M-CSF might drive the expression of DC-SIGN in tissue-resident macrophages in noninflamed tissues (homeostasis). Along this line, the ability of fibroblasts to modulate DC-SIGN expression on monocytes in an M-CSF-dependent manner (this manuscript), and the increased tissue repair and homeostasis observed in transgenic DC-SIGN mice after eradication of infectious agents (48), further support such a hypothesis.…”
Section: Dc-sign Expression On Tam Might Contribute To Maintenance Ofsupporting
confidence: 53%
“…21,37 hSIGN, hSIGNxDEREG mice, OT-I and OT-II tg were bred at the animal facilities of Twincore (Hannover, Germany) or VU University (Amsterdam, Netherlands) under specific pathogen-free conditions and used at 8-16 weeks of age. All experiments were performed according to institutional and national guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] As no functional homolog of DC-SIGN exists in mice, 20 we generated humanized mice expressing human DC-SIGN (hSIGN) on conventional DCs. 21 Importantly, delivery of antigens via anti-DC-SIGN monoclonal antibodies (aDC-SIGN) enhances T cell responses in vitro and in vivo. 18,19,22,23 An advantage of targeting antigens to CLRs is the possibility to modify antigens with the natural ligands of CLR, i.e., carbohydrates, which are small compared to antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and epidemiological studies have also implicated a role for these lectins in vivo in response to pathogenic infection. Recent studies using DC-SIGN transgenic mice showed protection and prolonged survival of mycobacterial infection (27). In addition, genetic analysis revealed that individuals homozygous for specific polymorphisms in the L-SIGN repeat domain had a lower risk of severe acute respiratory syndrome coronavirus infection (28).…”
mentioning
confidence: 99%